Revisita à Arquitectura Regional em Portugal. Processos de reinterpretação, no contexto de um núcleo de investigação - Bruno Plasencia e Quelhas (2021)
This dissertation results from work conducted within the scope of a research group, created with the objective of analysing the impact of the transformative processes of the last 60 years on Portuguese territory. This work uses as a basis the database developed throughout the travels of the Survey on Portuguese Regional Architecture, published in "Arquitectura Popular em Portugal" (1961/2004). The dissertation will contribute to the group's future work by exploring the body of existing literature and knowledge. Before reporting on the revisit, the dissertation explores the traditional definitions of popular architecture by examining the work of a set of authors who have studied this question, from Carlos Flores (1973) to Rudofsky (1977), from Rapoport (1969) to "Arquitectura Popular em Portugal" itself (1961/2004). Then, the Survey is contextualized in the moment that created it and the works that preceded it, as well as its potential and limitations as a basis for this work. After this theoretical framework, the dissertation first describes how the group originated and what were its motivations, and then provides an account of the group's field work, which this dissertation uses to investigate the transformations of popular architecture and territory since the Survey was conducted: the distance in Montes, the communitarianism in Santo André, the centrality in São João da Pesqueira and the heritage of the granaries of Lindoso. Articulating the theoretical framework and the field work, the dissertation reflects, globally, on the transformation of the territory and on the operability of the definitions of popular architecture. In this way, it opens possibilities for future research, both individually and within the group.